Program Design Summary Report - Jennifer Mersman::::::; Michael V. Nguyen:::::: (2024)
The report offers a summary of the faculty-led program design initiative. Launched in May 2023, this initiative is centered on the Culture and Needs Assessment (CNA) process, which is crucial for the enhancement of academic programs through detailed analysis and inclusive participation.